Where the mountain meets the moon - Lin, Grace (New York : Little Brown, 2009)
Minli, an adventurous girl from a poor village, buys a magical goldfish, and then joins a dragon who cannot fly on a quest to find the Old Man of the Moon in hopes of bringing life to Fruitless Mountain and freshness to Jade River.
Newbery Medal Honor Book, 2010.
Keywords: Fairy tales; Dragons -- Fiction; Moon -- Fiction